2021
DOI: 10.3390/pathogens10081051
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Developing Plant-Derived Candidate Vaccines and Biologics against Emerging Coronavirus Infections

Abstract: The emerging human coronavirus infections in the 21st century remain a major public health crisis causing worldwide impact and challenging the global health care system. The virus is circulating in several zoonotic hosts and continuously evolving, causing occasional outbreaks due to spill-over events occurring between animals and humans. Hence, the development of effective vaccines or therapeutic interventions is the current global priority in order to reduce disease severity, frequent outbreaks, and to preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 128 publications
2
28
0
Order By: Relevance
“…It is being developed by British American Tobacco company through Kentucky BioProcessing unit (KBP, biotech subsidiary in the US). Besides, Medicago Inc. (Quebec City, QC, Canada) is also developing virus like particles (VLPs) ( NCT04636697 ) to combat SARS-COV-2 using N. benthamiana [429] . They have successfully developed VLPs having structural similarity with actual corona virus using Covid-19 spike protein and lipid membrane of Nicotiana benthamiana plant.…”
Section: Therapeutic Targets For Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…It is being developed by British American Tobacco company through Kentucky BioProcessing unit (KBP, biotech subsidiary in the US). Besides, Medicago Inc. (Quebec City, QC, Canada) is also developing virus like particles (VLPs) ( NCT04636697 ) to combat SARS-COV-2 using N. benthamiana [429] . They have successfully developed VLPs having structural similarity with actual corona virus using Covid-19 spike protein and lipid membrane of Nicotiana benthamiana plant.…”
Section: Therapeutic Targets For Sars-cov-2mentioning
confidence: 99%
“…Notably, it exhibited a significant increase in amount of SARS-CoV-specific antibodies after immunization in mice model. It can be concluded that the plant based vaccines developed so for have shown promising results in pre-clinical trials [433] , [434] . Hence, any continued efforts in this direction might result in plant based safe vaccines for SARS-CoV-2 in near future.…”
Section: Therapeutic Targets For Sars-cov-2mentioning
confidence: 99%
“…Antibody therapy has been studied as an additional way to provide protection against SARS‐CoV‐2, preventing hospitalization and death by intercepting the virus and neutralizing it before the virus binds to cells. [ 121 ] There are different approaches, and various attempts reported using naturalizing antibodies and nanobodies for prevention and treatment of COVID‐19. [ 22 ] Several strategies have gained emergency authorization or are in clinical trials at various stages.…”
Section: Traditional Approaches Of the Biological Sciences And Drug D...mentioning
confidence: 99%
“…Moreover, the company iBio Inc. is working on a plant-based vaccine candidate designed to overcome the current challenges of first-generation vaccines (durability, access, and variant inclusion) and is currently in the pre-clinical trial phase. A plant-based vaccine candidate developed by Kentucky BioProcessing (owned by British American Tobacco) company with the potential to be stable at room temperature (a significant advantage for healthcare systems) is to date in phase 1/2 of clinical trial [3,4], while a further plant-based vaccine candidate (phase 1) is owned by a spin-off company from the faculty of pharmaceutical sciences Chulalongkorn University (Thailand).…”
Section: Introductionmentioning
confidence: 99%